Cycloastragenol promotes dorsal column axon regeneration in mice - Zihan, Tao; Wenwen, Teng; Yanxia, Ma; Saijilafu, (Frontiers in Cellular Neuroscience, 2025)
IntroductionCycloastragenol (CAG) has a wide range of pharmacological effects, including anti-inflammatory, antiaging, antioxidative, and antitumorigenic properties. In addition, our previous study showed that CAG administration can promote axonal regeneration in peripheral neurons. However, whether CAG can activate axon regeneration central nervous system (CNS) remains unknown.MethodsHere, we established a novel mouse model for visualizing spinal cord dorsal column axon regeneration involving the injection of AAV2/9-Cre into the lumbar 4/5 dorsal root ganglion (DRG) of Rosa-tdTomato reporter mice. We then treated mice by intraperitoneal administration of CAG.ResultsOur results showed that intraperitoneal CAG injections significantly promoted the growth of vitro-cultured DRG axons as well as the growth of dorsal column axons over the injury site in spinal cord injury (SCI) mice. Our results further indicate that CAG administration can promote the recovery of sensory and urinary function in SCI mice.ConclusionTogether, our findings highlight the therapeutic potential of CAG in spinal cord injury repair.